Методи психологічного впливу на ефективність тренувальної діяльності в спорті вищих досягнень - Демидович, Олександр Сергійович; Demydovych, Oleksandr Serhiyovych (Ірпінь, 2024)
У кваліфікаційній роботі представлені дані щодо змін ефективності тренувального процесу представників єдиноборств, зокрема тхеквондо ВТФ під впливом аутогенного тренування. Під час застосування аутогенного тренування у тренувальному процесі, спостерігаються позитивні зміни до покращення психологічних та фізичних показників спортсменів. Встановлено, що під дією аутогенного тренування покращує психологічні показники, а саме: емоційна стійкість, мотивація досягнення, впевненість.

The qualification paper presents data on changes in the effectiveness of the training process of representatives of martial arts, in particular taekwondo of the WTF, under the influence of autogenic training. During the application of autogenic training in the training process, positive changes are observed to improve the psychological and physical indicators of athletes. It has been established that under the influence of autogenic training improves psychological indicators, namely: emotional stability, motivation to achieve, confidence.
Methods of psychological influence on the efficiency of training activities in high-performance sports
Keywords: представники єдиноборств; психологічні показники; тхеквондо; аутогенне тренування; representatives of martial arts; psychological indicators; taekwondo; autogenic training